2022
DOI: 10.3390/children9121943
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrical Impedance Analysis-Derived Phase Angle and Body Composition Are Predictors of Health-Related Fitness in Children and Adolescents with Obesity

Abstract: There is little evidence in children and adolescents with obesity of the relationships between muscle strength/cardiorespiratory fitness (both components of health-related fitness = HRF) and body composition. Body composition and HRF were studied in 281 children and adolescents with obesity to explore their mutual relationship and to identify the predictors of HRF. By performing a bioelectrical impedance analysis (BIA), the fat-free mass (FFM) and percentage of body fat (%BF) were calculated, and the phase ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Though no statistical differences between groups were recorded, the means per group ( Table 8 ) of the BMI exceeded the WHO guidelines [ 19 ]. Recent research shows similar findings among children without intellectual disability [ 20 , 21 ] and with intellectual disability [ 22 ]. The combined prevalence of overweight and obesity among European teenagers is 22–25% [ 23 ].…”
Section: Discussionmentioning
confidence: 55%
“…Though no statistical differences between groups were recorded, the means per group ( Table 8 ) of the BMI exceeded the WHO guidelines [ 19 ]. Recent research shows similar findings among children without intellectual disability [ 20 , 21 ] and with intellectual disability [ 22 ]. The combined prevalence of overweight and obesity among European teenagers is 22–25% [ 23 ].…”
Section: Discussionmentioning
confidence: 55%
“…PhA for the trunk, leg, and whole body had significant negative correlations with %BF in each sex, and positive correlations with free fat mass in males. Another study found that PhA was a predictor of health-related fitness in children and adolescents with obesity ( 32 ). Moreover, PhA is an indicator of cellular health in chronic inflammatory states, which has been recommended as a prognostic marker of morbidity and mortality in various chronic inflammatory states, including obesity ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with sarcopenia, postoperative patients, chronic kidney disease patients, critically ill patients, and malnourished patients, phA can predict mortality [ 5 , 9 , 10 , 14 , 22 ]. The phA has also been studied in children and adolescents and has the potential to be a marker of muscle strength index [ 23 ].…”
Section: Introductionmentioning
confidence: 99%